(untitled) (Economic and Political Thought, 2018)
The relations between the European Union (EU) and the African, Caribbean and Pacific Group of States (ACP) are an example of an extremely developed model of the EU cooperation with developing countries. Over the 60-year period, it has been governed by many agreements establishing special forms of relations between the parties, creating its own institutional system of these relations, mechanisms of financial support and trade exchange. Currently, the reciprocal relations are maintained on the basis of the Partnership Agreement, concluded on 23 June 2000 in Cotonou. Its assumptions, however, expire on 29 February 2020, and the approaching end of the Cotonou Agreement raises questions about the future of the relations between the EU and the ACP group. Firstly, The article focuses on discussing the current state of implementation of the Cotonou Agreement, in particular the dimension of trade and economic cooperation since it will determine the most important future negotiations between the EU and the ACP group. Secondly, the article is based on the analysis of unofficial negotiation positions of both the EU and the ACP group, the separateness of which is so important that it does not bode well for conversations scheduled to start in 2018.